Scaling up infrastructure investment in the Philippines role of public private partnership and issues. (Metro Manila, Philippines Asian Development Bank, 2017)
The objective of this paper is to outline issues related to the choice between public procurement (including overseas development assistance) and public private partnerships (PPPs) as well as implementation and monitoring of PPP projects and fiscal risks in general and more specific to the case of the Philippines. It looks into the Philippine experience of embarking on PPP modality from various dimensions and points out key challenges that will need to be overcome. This publication also provides policy recommendations for the government to mobilize private sector expertise and resources to improve PPP project screening, approvals, and implementation.
Keywords: Finance -- Philippines; Fiscal policy -- Philippines; Industry policy -- Philppines; Philippines -- Public administration; Electronic books